If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -13 = -10 Reorder the terms: -13 + 3z = -10 Solving -13 + 3z = -10 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 3z = -10 + 13 Combine like terms: -13 + 13 = 0 0 + 3z = -10 + 13 3z = -10 + 13 Combine like terms: -10 + 13 = 3 3z = 3 Divide each side by '3'. z = 1 Simplifying z = 1
| 4x-2y=-12 | | -2+6=4v-6v | | 42m^2-29mn-5n^2= | | 9x+-2=4x+9 | | 0=8x+39 | | Y-2.8=2.2 | | Y-2.8=2.3 | | 15+8k=-34 | | 2x+3-x=6 | | 7y^2-4y-6= | | 6x+-1=x+13 | | s+2.5=6.25 | | 6(2X-4)=-32 | | -38=5x-x+10 | | 3x+(x+2)=20 | | 10x+-1=8x+6 | | 3x+9-x+4-2x=18 | | 9-24u+16u^2= | | 5x+-1=2x+11 | | 81-18s-3s^2= | | 7(x+3)-2(3x+1)=25 | | y^2+64=0 | | 38-30v=32 | | 150-5s-5s^2= | | 12x+-4=8x+24 | | 4x+0y+2z=24.94 | | 11-6x^2-31x= | | 6x+4y+1z=36.39 | | -7+7x-x=-1 | | 13-12d^2-35d= | | 10x+-6=7x+9 | | x=4.2375+-0.5y |